Core temperature and sweat responses in professional women's tennis players during tournament play in the heat - Tippet, M. L.; Stofan, J. R.; Lacambra, M.; Horswill, C. A. (Journal of Athletic Training, 2011)
Context: Tennis is often played in hot, humid environments, intensifying the thermoregulatory strain placed on the athletes. As a safety measure, some tennis organizations allow for a 10-minute break in play between the second and third sets when environmental conditions are extreme. However, the actual effect of these breaks in reducing core temperature is unknown.